DRYING KINETICS OF APRICOTS KERNELS - Boestean Olga (Journal of Engineering Science (Chişinău), 2018)
In this paper, we proposed convective and combined methods for drying wet kernels of apricot stones. Kernels of apricot stones are a very ambiguous food product, during their heat treatment in them occurs not only the loss of mass due to the removal of moisture, but also the loss of mass due to biochemical changes occurring at high temperatures. It was experimentally established that the drying process should be carried out in two stages: the first stage lasts until the critical moisture content of 110 % (by total weight of solids) is reached and it should be implemented by convective energy supply (100 °С). The second stage lasts until the equilibrium moisture content of 30 % is reached, using a combined energy supply (convention + UHF) with the strength of the electromagnetic field E = 1.8 * 104 V·m-1.